2011
DOI: 10.1007/s11192-011-0455-1
|View full text |Cite
|
Sign up to set email alerts
|

Research involving women and health in the Medline database, 1965–2005: co-term analysis and visualization of main lines of research

Abstract: This paper shows the main lines of research concerning health and women, as registered in the Medline database, broken down into four 10-year periods: . The units of analysis used were the Medline ''MeSH'' major terms, processed by means of co-term analysis. For graphic representation, the social network approach was used, with pruning performed by Pathfinder Networks (PFNET), so as to concentrate the displays. Factor analysis was used to group the descriptors and identify the main lines of research involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…In the light of previous experience involving keyword frequency and links (Zulueta et al, 2011;Cantos-Mateos et al, 2012Muñoz-Écija et al, 2017), we tagged each cluster, obtaining what would be the seven lines of research that support the knowledge structure of graphene research worldwide: Fundamental Research, Functionalization and Biomedical App lications, Technology and Devices, Materials Science, Energy Storage, Optics, and Chemical Properties and Sensors. According to the clustering algorithm used, the order of the clusters or research lines is determined by their number of keywords.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of previous experience involving keyword frequency and links (Zulueta et al, 2011;Cantos-Mateos et al, 2012Muñoz-Écija et al, 2017), we tagged each cluster, obtaining what would be the seven lines of research that support the knowledge structure of graphene research worldwide: Fundamental Research, Functionalization and Biomedical App lications, Technology and Devices, Materials Science, Energy Storage, Optics, and Chemical Properties and Sensors. According to the clustering algorithm used, the order of the clusters or research lines is determined by their number of keywords.…”
Section: Resultsmentioning
confidence: 99%
“…It is furthermore able to bring to light new developments of a research line over time (Peters and van Raan, 1993a,b) and help policy makers understand the complex interrelations of science and their implications for effective research planning (He, 1999). Although co-word analysis has gradually been improved upon, while not all of its limitations have been overcome (Wang et al, 2012), this type of analysis can reveal the intellectual underpinnings of a wide variety of domains: chemistry (Callon et al, 1991), data retrieval (Ding et al, 2001), the fuzzy logic field (López-Herrera et al, 2010), women and health (Zulueta et al, 2011), keyword analysis (Cantos-Mateos et al, 2012), human intelligence networks (Wang et al, 2012), and stem cells (Cantos-Mateos et al, 2014). A recent study applied it to study the intellectual structure of nanotechnology and its evolution (Muñoz-Écija et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…The resulting domestic co-authorship network had a giant interconnected component of 1,782 authors, out of which around 239 (13.41 percent) were identified to be faculty members at Pakistani universities/institutes. For the graphic representation of the network, a social network approach was used; with pruning performed by the Pathfinder Network Scaling and a layout determined by Fruchterman-Rheingold and Spring-Embedder type algorithms (Moya-Anegón et al, 2007;Vargas-Quesada et al, 2010;Zulueta et al, 2011). The procedure was accomplished using the Sci 2 software (Sci2 Team, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…While prior research has explored and tested gender differences in scientific publishing and research performance in co-authorship networks related to different countries and different scientific fields (Arensbergen et al, 2012;Barrios et al, 2013;Borrego et al, 2010;Kretschmer et al, 2012;Mozaffarian and Jamali, 2008;Sotudeh and Khoshian, 2013;Zulueta et al, 2011), yet they lack an insight about the potential moderating role of gender on the relationship between structural social capital and research performance in co-authorship networks. An exception was an earlier paper by Ö zel et al (2009), which examined the impact of gender on patterns of scientific collaboration in social sciences in Turkey and found that male authors collaborate more (most often with males only) and females collaborate less (those who collaborate do however involve in inter-gender collaborations significantly more often than males).…”
Section: Introductionmentioning
confidence: 99%
“…La literatura muestra precedentes en el análisis de coocurrencias de palabras. Zulueta et al (2011) muestran las líneas de investigación sobre salud y mujer a través de Medline, utilizando técnicas de visualización de redes y análisis factorial. Zhang et al (2012) utilizan el análisis de co-palabras y de redes sociales para estudiar la investigación sobre adherencia de los pacientes a los tratamientos.…”
Section: Antecedentesunclassified